The Effect Of Back Massage Therapy On Rheumatic Pain In The Elderly In The Geriatric Clinic Kesdam Cijantung Hospital, East Jakarta Year 2019 - Susilowati, Susilowati; Susanti, Fajar; Samsuni, Samsuni (Journal of Ageing And Family, 2021)
Rheumatic disease is a chronic joint inflammatory disease caused by an autoimmune disorder. Pain is a clinical complaint most frequently encountered by nurses. This study aims to determine the comparison of the results of back message therapy and not back message therapy with pain in elderly rheumatism. This study is a quantitative study with a quasi-experimental research design made using a non-equivalent group design with pre and post tests. The research sample was 18 respondents. The sampling technique used purposive sampling. Data collection using experimental method. The instrument for measuring the level of pain uses a numerical rating scale (NRS) . From the results of statistical analysis using the Independent Sample Test, it is known that the average difference in the measurement results of back message therapy in the pre category of 5.22 and post is 2.00 with p value = 0.000 (<0.05), while there is a difference of pre 5, 17 and post 3.50 on no back message therapy which obtained p value = 0.000 (<0.05). It was concluded that there was a significant difference in pain in elderly arthritic patients who took back message therapy and did not follow back message therapy. It is important for the results of this study that health workers teach back message therapy for the elderly who experience pain because this is a very effective therapy for people with rheumatism.Keywords: Back Message, Rheumatic Pain, Elderly